2022
DOI: 10.15739/irjpeh.22.004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Romanian version of coparenting relationship scale

Abstract: Studies show that children from divorced families are more likely to experience emotional and behavioral problems, which is why researchers have focused on finding factors that facilitate children's post-divorce adaptation. One of these factors is coparenting. Thus, to measure the quality of coparenting, the Coparenting Relationships Scale (CRS) was developed. The aim of this study was to adapt and validate this scale for the Romanian population. It was used a combination between the procedure of back-translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The research presented in this article aimed to establish the Polish adaptation of the CRS. Previous studies have indicated that the CRS is a highly effective tool for assessing parental cooperation (Carvalho et al, 2018; Dumitriu et al., 2022; Favez et al, 2021; Feinberg et al, 2012; Ju et al, 2023; Lee et al, 2021; Pinto et al, 2019). While it has been adapted in several countries, there was a lack of such an instrument for a population of Polish mothers and fathers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The research presented in this article aimed to establish the Polish adaptation of the CRS. Previous studies have indicated that the CRS is a highly effective tool for assessing parental cooperation (Carvalho et al, 2018; Dumitriu et al., 2022; Favez et al, 2021; Feinberg et al, 2012; Ju et al, 2023; Lee et al, 2021; Pinto et al, 2019). While it has been adapted in several countries, there was a lack of such an instrument for a population of Polish mothers and fathers.…”
Section: Discussionmentioning
confidence: 99%
“…In this project, we decided to address this gap, and the analysis followed a structured approach, including an initial assessment of data quality related to examining inter-item correlations and the reliability of the full CRS, full CRS subscales, and the Brief-CRS. Furthermore, it entailed an evaluation of various theoretical models based on proposals available in the CRS literature, encompassing both the original version (Feinberg et al, 2012) and its adaptations (Carvalho et al, 2018; Dumitriu et al, 2022; Favez et al, 2021; Ju et al, 2023). Subsequently, we conducted a gender invariance measurement analysis for the Polish sample and two cultural invariance measurement analyses for American-Polish and Swiss-Polish samples separately.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations